ANALISIS BUKU AJAR BAHASA ARAB KELAS VI MADRASAH IBTIDAIAH TERBITAN KARYA TOHA PUTRA - Azhari, Afifa Wijdan (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2018)
Textbooks must meet the criteria for suitable textbooks that have been set by BSNP, and the teaching material in them is quality teaching material. The purpose of this study was to determine the Arabic language textbook class VI Issued by Toha Putra. whether the textbook meets BSNP standards and meets the quality of the textbook based on aspects of selection, gradation, presentation and repetition. The method used is documentation study and literature study. Based on the results of this study the book is a book that is not in accordance with BSNP standards and meets the quality of teaching materials based on aspects of selection, gradation, presentation, and repetition.